Pengaruh Ukuran Partikel terhadap Sifat Fisikokimia Tepung Ampas Tapioka Kaya Serat - Ranti Futiawati (JURNAL PANGAN, 2016)
Tapioca cake is solid residue from tapioca extraction process consists of high fiber and remaining non-extracted starch. Tapioca cake can be used as a source of fiber-rich food ingredient. The researchwas aimed to analyze the effect of particle size and washing frequency of ground tapioca cake on physicochemical properties of the resulted flour. The flour was prepared by grounding the tapioca cake usingdisc mill, sieved to different particle size (40–60, 60–80, 80–100, and >100 mesh) and then washed withdifferent frequencies (without washed (0), washed 1, 2, 3, 4, 5, and 6 time). The physicochemical propertiesof flour evaluated were moisture content, starch content, total dietary fiber content, and rheologicalproperties. The results showed that different particle size of ground tapioca cake with and washing frequencyinfluenced the starch content, total dietary fiber content, and rheological properties of tapioca cakeflour. Ground tapioca cake with particle size of 60–80 mesh and washed four times resulted in the flour withmoisture, starch, and total dietary fiber content of 9,81, 27,36, and 44,12 percent; respectively, and withrheological properties of peak viscosity of 3266 cP, breakdown viscosity of 801 cP, and setback viscosityod 1725 cP.